Teachers' Strategies in Realising National Resilience through Strengthening Civic Disposition: A Study in State Junior High Schools in Gorontalo City - Zulaecha Ngiu; Rahmatiah Rahmatiah; Yayan Sahi (Dinasti International Journal of Education Management And Social Science, 2025)
This study aims to identify the strategies of Civic Education teachers in strengthening national resilience through the development of civic disposition in Junior High Schools in Gorontalo City. This research uses qualitative methods with data collection techniques through observation, interviews, and documentation. Observation was conducted to understand the extent of the strategies applied in strengthening civic disposition during the learning process. Interviews were conducted with Civics teachers as informants to gain an in-depth understanding of their strategy implementation, while documentation was used to record relevant data, such as photos and other important information. The results showed that national resilience can be effectively enhanced through the implementation of Pancasila values-based civic disposition. Collaborative support between the Gorontalo City Education Office and junior high schools in Gorontalo City is instrumental in shaping students' religious and nationalist characters. Through a programme that emphasises tolerance, responsibility and social care, students are encouraged to apply civic concepts in real life, thus strengthening their national identity. However, there are barriers in implementing this strategy, such as limited resources and the influence of social media that can distract students from civic values. The conclusion of this study shows that Civics teachers' strategies, including the teaching of Pancasila values and interactive learning activities, play an important role in shaping a generation that understands its rights and obligations as citizens, and contributes positively to national resilience and the nation's progress.